2012
DOI: 10.1002/ange.201200409
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Nanomaterials that Mimic the Food Effect: Controlling Enzymatic Digestion for Enhanced Oral Drug Absorption

Abstract: Leichte Kost: SiO2‐Lipid‐Hybridmikropartikel mit nanostrukturiertem Inneren wurden aus Emulsionen submikrometergroßer mesoporöser und nichtporöser SiO2‐Nanopartikeltemplate erzeugt. Mit den lipidbasierten Mikropartikeln kann die orale Gabe von Pharmaka simuliert und die Wirkstoffabsorption durch Steuerung des enzymatischen Verdaus von Lipidkolloiden gesteigert werden (○ Öllösung, ▴ Lipid‐Nanopartikel‐Hybrid, □ Lipid, eingeschlossen im Hybrid).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…When aerosil or ludox are tested in presence of fat globules and a surfactant (lecithin), the silica particles locate at the interface between water and fat, coating the fat globule. This type of behavior produces a much faster and more complete hydrolysis of fats than in model systems in which the nanomaterial is not present [ 17 ]. The same authors also verified that the size of the particles, their topology, the material to fat ratio and the surface charge are factors that modify the surface properties and therefore the ability of the lipase to access the substrate and vary the hydrolysis rate [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…When aerosil or ludox are tested in presence of fat globules and a surfactant (lecithin), the silica particles locate at the interface between water and fat, coating the fat globule. This type of behavior produces a much faster and more complete hydrolysis of fats than in model systems in which the nanomaterial is not present [ 17 ]. The same authors also verified that the size of the particles, their topology, the material to fat ratio and the surface charge are factors that modify the surface properties and therefore the ability of the lipase to access the substrate and vary the hydrolysis rate [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, oil/water microemulsion was applied in the morphology control, not suitable for scalable synthesis. Spray drying, on the other hand, is a facile method for the synthesis of multi-shelled metal oxides (Zhou et al, 2013) and the assembly of colloidal silica nanoparticles into microspheres (Tan et al, 2012). When Ludox silica templates, resorcinol and formaldehyde as carbon precursors were used via the spray drying method, silica/polymer microspheres and subsequently mesoporous carbon microspheres were synthesized (Li et al, 2014), with a surface area below 1,200 m 2 g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Silica-lipid hybrid (SLH) microparticles are a kind of solid system based on silica particles and oil-in-water emulsion, which were reported for the first time by Simovic et al ( 21 ) and Tan et al ( 22 ). The researches show that the SLH microparticles significantly improve the solubility and stability of the water-insoluble drugs, and also enhance the oral absorption of drugs in experimental animals by simulating food effects ( 21 - 23 ). In another study ( 24 ), researchers found that the ibuprofen in SLH microparticles prepared by spray drying has higher solubility than the control group during a two-step dissolution and its bioavailability increased nearly 1.95-fold compared to the commercial tablets in clinical trials.…”
Section: Introductionmentioning
confidence: 99%